Acute necrotizing colitis - Matteucci, Pablo; Porras, Yamandú; Falconi, Luis; Sanguinetti, Jorge (Cirugía del Uruguay, 1976)
There are five cases of acute necrotizing colitis, segmentary process of the colon, without vascular disturbs. To this purpose we study the clinic and pathological characteristics of thig unusual affection, emphasizing its seriousness and pointing out sone ways to its treatment.